Make the environment protect you from disease: elevated CO2 inhibits antagonists of the fungus-farming termite symbiosis - Schmidt, Suzanne; Bos, Nick; Murphy, Robert; Koné, N’Golo A.; Silué, Kolotchelema S.; Meyling, Nicolai V.; Poulsen, Michael (Frontiers in Ecology and Evolution, 2023)
Abstract Fungus-farming termite colonies maintain monoculture fungus combs in underground chambers without apparent problems with diseases. Multiple lines of defense contribute to the suppression or removal of antagonists of the symbiosis, but the role of the termite-manipulated environment within mounds has yet to be tested. Specifically, termite mounds have extremely high levels of CO2 compared to atmospheric levels . We tested the effect of 5% CO2 on the growth of fungal crop from Macrotermes bellicosus colonies, generalist fungi that could challenge the symbiosis, as well as a specialist stowaway fungus, Pseudoxylaria. For sporulating fungi, we also quantified the effects on conidia production. We found that elevated CO2 significantly reduces mycelial growth and conidia production of generalist fungi Aspergillus sp., Beauveria bassiana and Metarhizium brunneum, whereas it overall had a net positive effect on the growth of the fungal crop Termitomyces and Pseudoxylaria; albeit, with variation between fungal strains within genera. Our findings point to elevated CO2 being of adaptive significance to the fungus-farming termite symbiosis as an additional layer of defense that helps keep termite fungus gardens free from fungal infections. The mound-building activities that make termites ecosystem engineers may thus also generate environmental conditions that impact the fate of fungi inhabiting the extended phenotypes that massive termite mounds represent.